A participação política em tempos de globalização: o Fórum Social Mundial inaugura o movimento social global - Ana Maria Prestes Rabelo (2006)
The world lives in an acellerating narrowment process of its bondaries, phisical, economics, political and cultural ones. At the same time the sistemics inequalities are deeper, dividing the world in North and South. This process is called globalization, and its contradictory caracterhas hegemonic and counter hegemonic faces. The global governance system emergence, lidered by the capitalism central states and international agencies, simultaneously with the surgement of a vast antiglobalization political participation movement, made us ask about therelationship between the two phenomena. Throghout the World Social Forum data analysis, we intend to understand the globalization of the political participation and its role to a counter-hegemonic globalization.